Restorative Justice for Traffic Crimes Resulting in Fatalities : Ethical and Legal Considerations - Usman, Rachmadi; Humah, Darsis (Ipso Jure, 2025)
The application of restorative justice (RJ) in fatal traffic accident cases in Indonesia still faces legal and normative challenges. This study uses a normative juridical method to analyze existing regulations and compare retributive justice with restorative justice within the Indonesian legal system. The findings show that while RJ offers a solution based on relationship restoration, Indonesia's legal system, dominated by retributive justice, still prioritizes criminal punishment as the primary resolution. Legal gaps and normative ambiguities are the main obstacles to the application of RJ in fatal accident cases. In conclusion, to optimize the application of RJ, legal reforms are needed to integrate RJ into Indonesia's judicial system, without neglecting victims' rights.